Gestão do conhecimento em empresa pública: práticas e iniciativas adotada pelo Poupatempo - Ruggieri, Ruggero (2019)
The understanding of the knowledge society necessarily goes through the comprehension and analysis of transformation processes in the treatment of information and knowledge that has been occurring in contemporary organizations. The importance and impact of his phenomenon, specifically in public administration organizations, is of high relevance, since the development of any society necessarily goes through the quality of the provision of public services to its constituent elements. The aim of this research is to verify how the public company of São Paulo Poupatempo effected the adoption, operationalization and management of the policy of knowledge management and innovation of the Decree N. 53.963/2009 (SAO PAOLO, 2009), which instituted the management policy of the Knowledge and innovation for public organizations in São Paulo. This qualitative descriptive research employed as a research instrumental semi-structured interview, direct observation and documental analysis of public records. We obtained 32 responses from managers regarding the identification of practices and initiatives of knowledge Management (KM) implemented in the Poupatempo and 70 responses of technical employees regarding their operationalization. The importance of prioritizing knowledge for the implementation of KM, in Poupatempo obtained a high number of argumentations in the analyses carried out, mainly regarding the need to distribute new knowledge to the employees, Characterized in one of the main reasons why new knowledge is the priority of the KM developed by Poupatempo. In addition, we emphasize the importance of implementing a policy of knowledge management with clearly defined guidelines and strategies, aiming to expedite the process of institutionalization of KM in the public administration of Poupatempo.